Sony / Muhammad Safwan Najmi Shaari - Najmi Shaari, Muhammad Safwan (2022)
This assignment is about identifying the problem with the product. The company that I have chosen is SONY Group Corporation. From their variety of products, I have chosen the Sony DVR DV-R10 (Dashcam Camera) to analyse. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the Sony DVR DV-R10. The main problem I recognised on this Sony DVR DV-R10 is that the device only records what happened in front of the car with the angle of 140 degree and there are some blind spots that the dashcam not cover for the safety of the vehicle. From the problem, I can come up with the best solution to enlarge the viewing angle of the dashcam. Then the device will record what happens in front of the car at every angle and prevent blind spot areas for car security purposes.